2006
DOI: 10.1158/0008-5472.can-05-4193
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Mediated Tumor Invasion: a Multidisciplinary Study

Abstract: The acid-mediated tumor invasion hypothesis proposes altered glucose metabolism and increased glucose uptake, observed in the vast majority of clinical cancers by fluorodeoxyglucose-positron emission tomography, are critical for development of the invasive phenotype. In this model, increased acid production due to altered glucose metabolism serves as a key intermediate by producing H + flow along concentration gradients into adjacent normal tissue. This chronic exposure of peritumoral normal tissue to an acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
659
1
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 728 publications
(687 citation statements)
references
References 25 publications
14
659
1
13
Order By: Relevance
“…Firstly, it enables cancer cells to adapt to hypoxic conditions as the premalignant lesion grows progressively further from the blood supply. Secondly, the glycolytic phenotype contributes to the acidification of tumour microenvironment, which facilitates tumour invasion (Gatenby and Gawlinski, 1996;Schornack and Gillies, 2003). This metabolic transition towards glycolysis is also seen in human cancer cell lines such as Hela cells, in which minor amounts of glucose are prone to the TCA cycle, the majority being converted to lactate (Reitzer et al, 1979).…”
Section: Mitochondrial Physiology In Cell Proliferation and Tumour Prmentioning
confidence: 99%
“…Firstly, it enables cancer cells to adapt to hypoxic conditions as the premalignant lesion grows progressively further from the blood supply. Secondly, the glycolytic phenotype contributes to the acidification of tumour microenvironment, which facilitates tumour invasion (Gatenby and Gawlinski, 1996;Schornack and Gillies, 2003). This metabolic transition towards glycolysis is also seen in human cancer cell lines such as Hela cells, in which minor amounts of glucose are prone to the TCA cycle, the majority being converted to lactate (Reitzer et al, 1979).…”
Section: Mitochondrial Physiology In Cell Proliferation and Tumour Prmentioning
confidence: 99%
“…8 Using dorsal window chambers, we have demonstrated that acidic environments promote tumor invasion and growth by degrading adjacent extracellular matrix]. 9,10 Thus, we view the intratumoral environment as "niche engineering" wherein cancer cells, in response to Darwinian dynamics, generate an environment that promotes their own growth and invasion 11 at the expense of the stromal cells into which they invade. Acidosis also inhibits anti-tumor immunity and promotes immune editing.…”
Section: Introductionmentioning
confidence: 99%
“…12 From these observations, we have proposed the "acid-mediated invasion" model, wherein tumor-derived acid promotes remodeling of the extracellular matrix, while cancer cells contemporaneously become adapted and more resistant to acidity, compared to the stromal cells into which they invade. 10 However, the mechanism by which tumor cells adapt to this chronic acidosis is not yet fully known. This is a critically important question, as it is virtually axiomatic that, in order to thrive, cells in tumors must develop mechanisms of defense that render them insensitive to this acid challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of glucose metabolism regulate cancer metastasis by high glucose uptake, high lactate formation, low extracellular pH (pH e ) and reduction of intratumoral pH (Bhujwalla et al, 2002;Schornack and Gillies, 2003;Gatenby and Gillies, 2004;Gatenby et al, 2006). The acidic environment is produced by the activity of ion channels and transporters such as Na þ /H þ or Cl/HCO 3 exchangers (Klein et al, 2000;Saadoun et al, 2005).…”
Section: Introductionmentioning
confidence: 99%